108k views
5 votes
ASAP pleaseeee I reallly need it ❤️

ASAP pleaseeee I reallly need it ❤️-example-1

1 Answer

2 votes


(x^2)/(3)-(1)/(2)=(x)/(3)

Because there are 3 and 2 as the denominators. Find the lowest number that both 3 and 2 can divide without any quotients, which is 6.

Multiply all whole equation by 6.


(x^2)/(3)(6)-(1)/(2)(6)=(x)/(3)(6)\\2x^2-3=2x

We should get like this. Then move 2x to subtract.


2x^2-2x-3=0

Because the polynomial is a two-degree and a quadratic equation. We solve the value of x by either factoring, using the formula or completing the square.

But I'll use the Quadratic Formula instead as the factoring doesn't seem to work for the Quadratic Equation with square root answers.


x=(-b±√(b^2-4ac) )/(2a)

This is the formula of Quadratic Equation. Ignore the weird letter as it just randomly appears and can't be deleted.


x=(-(-2)±√((-2)^2-4(2)(-3)) )/(2(2)) \\x=(2±√(4+24) )/(4) \\x=(2±√(28) )/(4)\\x=(2±2√(7) )/(4) \\x=(1±√(7) )/(2)

Therefore, the answer is x = (1±√7)/2

User Appsum Solutions
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.